2014
DOI: 10.1038/jes.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the take-home pathway: Farmworkers and non-farmworkers and their children

Abstract: Background Organophosphate pesticides (OPs) are related to ill health among adults including farmworkers who are exposed to OPs as part of their regular work. Children of both farmworkers and non-farmworkers in agricultural communities may also be affected by pesticide exposure. Methods Study groups of 100 farmworkers with a referent child (aged 2 to 6 years) and 100 non-farmworkers with a referent child were recruited to participate in three data collection periods over the course of a year. At each collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
3
40
1
Order By: Relevance
“…Thus, concern has been raised with regard children residing near pesticide-treated farmlands, or whose parents are agricultural workers, because they have higher risk of developing cancer or other serious health problems [9,11,12,[16][17][18]. OP metabolites were seen at much higher levels for farmworkers and their children than non-farmworkers and their children during the agricultural season when OPs were in use [19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, concern has been raised with regard children residing near pesticide-treated farmlands, or whose parents are agricultural workers, because they have higher risk of developing cancer or other serious health problems [9,11,12,[16][17][18]. OP metabolites were seen at much higher levels for farmworkers and their children than non-farmworkers and their children during the agricultural season when OPs were in use [19].…”
Section: Introductionmentioning
confidence: 99%
“…One study of farmworkers in the state of Washington in the United States found that during the thinning season, urinary metabolites of organophosphate dimethyl pesticides were significantly higher in the children of farmworkers than in non-farmworker children [10]. In addition, among individuals who work in conventional agriculture where pesticides are used, pesticide concentrations have been found to be elevated in vehicle and house dust when compared to a reference population [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The ϳ200-household Yakima Valley community agricultural cohort studied here provides seasonal longitudinal measures of exposure to OPs using blood samples collected in the spring/summer of 2005 and winter 2006 for adults and children (31). Sequenced buccal samples from 117 adult individuals were used to determine proportional abundances of oral microbiome bacteria detected in buccal swabs.…”
mentioning
confidence: 99%
“…Sequenced buccal samples from 117 adult individuals were used to determine proportional abundances of oral microbiome bacteria detected in buccal swabs. Blood concentrations of azinphos-methyl have been determined by mass spectrometry in this family-based community pesticide exposure study (31). Samples were collected in spring/summer 2005 to measure pesticide exposure during the spring-to-summer fruit-thinning season, when the workers had a high likelihood of OP exposure.…”
mentioning
confidence: 99%